Implantação de uma proposta de automação na dispensação de medicamentos controlados como ferramenta para otimizar as vendas no varejo farmacêutico - Silva, Wesley Nelo da (2019)
Introduction: Pharmaceutical retail is driven by the constant pursuit of increased sales, where prescription drugs make up an important share. Thus, the insertion of an automation process in dispensing prescription drugs enables process optimization and increased customer turnover. and, consequently, the increase in sales that can generate the increase of profit to the pharmaceutical retail. Objective: To demonstrate how the automation of a prescription drug dispensing system can improve service time and increased sales within the pharmaceutical retail, presenting a proposal to implement an automation system for retail sales and measuring the quantity increased sales and reduced costs due to the automation of a prescription drug dispensing system. Methodology: This is a prospective, exploratory, multiple case study, conducted between July 1, 1919 and October 31, 1919, in the Midwest region of São Paulo, in five drugstores with high number of controlled drug dispensations. Results: It was observed that the automation method is more efficient in the sense of time, allowing the prospecting of new calls in relation to the traditional manual method. In the cost to perform the process, each service in the automation method, presented lower cost compared to the traditional manual method based on the São Paulo wage floor, both of the pharmacist and the drug clerk. Over a 7-hour period, the study showed that it was possible for employees to fill more medical prescriptions in the automation method compared to the traditional manual method. Conclusion: Automation has enabled time savings during the application of bureaucratic processes for filling medical prescriptions of controlled products, reducing costs in the execution of the process, optimizing the quality and reproduction of dispensing processes, faster and more organized data capturing, safety. customer information to comply with current legislation and consequently increased attendance, which may enable increased sales.